2014
DOI: 10.1186/1678-9199-20-30
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic neuromuscular action of a methanolic extract from the venom of Rhinella schneideri toad

Abstract: BackgroundRhinella schneideri, previously known as Bufo paracnemis, is a common toad in many regions of Brazil. Its venom exerts important cardiovascular effects on humans and other animals. Although this toad venom has been the subject of intense investigations, little is known about its neuromuscular activity.MethodsThe neurotoxicity of a methanolic extract of R. schneideri venom was tested on mouse phrenic nerve-diaphragm (PND) preparations mounted for conventional twitch tension recording – in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
1
16
0
1
Order By: Relevance
“…Previous studies showed that the methanolic extract of R. schneideri poison compounds are capable of affecting neurotransmission in avian and mammalian preparations. The recovery of the number of synaptic vesicles after 60 min of incubation with the methanolic extract of R. schneideri granular (parotoid) gland secretion indicates a transient increase in the neurotransmitter release, which is in accordance to the facilitation observed by Rostelato-Ferreira et al (2014) in PND preparations.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Previous studies showed that the methanolic extract of R. schneideri poison compounds are capable of affecting neurotransmission in avian and mammalian preparations. The recovery of the number of synaptic vesicles after 60 min of incubation with the methanolic extract of R. schneideri granular (parotoid) gland secretion indicates a transient increase in the neurotransmitter release, which is in accordance to the facilitation observed by Rostelato-Ferreira et al (2014) in PND preparations.…”
Section: Discussionsupporting
confidence: 77%
“…In their study, Rostelato-Ferreira et al (2014) reported that diaphragm preparations that were incubated with R. schneideri methanolic extract (50 µg/mL of granular gland secretion) responded with an increase in quantal content (release of acetylcholine) that was inhibited with a non-toxic concentration of ouabain (1 mg/mL), an inhibitor of the Na + / K + -ATPase, after 5 min prior to incubation, indicating that these effects were prevented through the inhibition of Na + -K + -ATPase activity of muscle motor innervation.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations